Worldwide prevalence estimates of lower urinary tract symptoms, overactive bladder, urinary incontinence and bladder outlet obstruction - Irwin, Debra E.; Kopp, Zoe S.; Agatep, Barnabie; Milsom, Ian; Abrams, Paul (BJU international, 2011)
Study Type – Symptom prevalence (prospective cohort) Level of Evidence 1b What’s known on the subject? and What does the study add? Few prevalence studies used current ICS LUTS symptom definitions and to our knowledge no studies exist that estimate total worldwide prevalence of reported LUTS symptoms. One of the primary goals of this analysis was to estimate current and future worldwide prevalence of LUTS among adults. Our estimation model suggests that LUTS are highly prevalent worldwide, with an increasing burden predicted over time. OBJECTIVE • To estimate and predict worldwide and regional prevalence of lower urinary tract symptoms (LUTS), overactive bladder (OAB), urinary incontinence (UI) and LUTS suggestive of bladder outlet obstruction (LUTS/BOO) in 2008, 2013 and 2018 based on current International Continence Society symptom definitions in adults aged ≥20 years. PATIENTS AND METHODS • Numbers and prevalence of individuals affected by each condition were calculated with an estimation model using gender‐ and age‐stratified prevalence data from the EPIC study along with gender‐ and age‐stratified worldwide and regional population estimates from the US Census Bureau International Data Base. RESULTS • An estimated 45.2%, 10.7%, 8.2% and 21.5% of the 2008 worldwide population (4.3 billion) was affected by at least one LUTS, OAB, UI and LUTS/BOO, respectively. By 2018, an estimated 2.3 billion individuals will be affected by at least one LUTS (18.4% increase), 546 million by OAB (20.1%), 423 million by UI (21.6%) and 1.1 billion by LUTS/BOO (18.5%). • The regional burden of these conditions is estimated to be greatest in Asia, with numbers of affected individuals expected to increase most in the developing regions of Africa (30.1–31.1% increase across conditions, 2008–2018), South America (20.5–24.7%) and Asia (19.7–24.4%). CONCLUSIONS • This model suggests that LUTS, OAB, UI and LUTS/BOO are highly prevalent conditions worldwide. Numbers of affected individuals are projected to increase with time, with the greatest increase in burden anticipated in developing regions. • There are important worldwide public‐health and clinical management implications to be considered over the next decade to effectively prevent and manage these conditions.